The Suboptimal Process of Teaching and Learning Hinduism in Java - Dharma Bhusana, I Wayan Hari; Gara, I Wayan (International Journal of Multidisciplinary Sciences, 2024)
Education plays a crucial role in achieving a dignified nation's civilization since the better the quality of a nation's education, the more aligned it is with the improvement of the nation's overall quality. In several areas, particularly outside of Bali, there is currently a phenomenon where Hindu students claim to study subjects related to other religions and even receive grades for those subjects, which are then included in their report cards as religious scores. On the other hand, there are religious institutions that are prepared to provide education for students who do not receive Hinduism education in their schools, even with the necessary facilities and amenities. However, Hindu students outside Bali still face challenges, such as a lack of Hinduism teacher and other factors, hindering their ability to study Hinduism education. Therefore, there is a need for the revitalization of Hinduism education.